(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : Colorectal carcinoma (CRC) is the most frequently observed malignancy worldwide. The incidence of CRC is 3.5% in Bangladesh. Conflicting data exist about the prevalence of HER-2/neu over expression in colorectal cancer ranging from 0 to 83%. The aim of this study was to evaluate the expression of Her-2/neu protein in colorectal cancers. Materials and methods: This descriptive cross-sectional study was conducted in the Department of Pathology of Chittagong Medical College, Chittagong, Bangladesh from 1st January 2017 to 31st December 2017. A total of 52 cases with a histopathological diagnosis of colorectal cancers included in the study as sample size, HER2 status was evaluated by immunohistochemistry (IHC) in formalin fixed, paraffin embedded tissue.Positive expression was assigned a score from 0–3+.IHCs were analysed with grades of colon cancers. Results: The mean age in this study was 47.62years range from 12 to 85 years ,53.8% were female. Among 52 specimens 30 (57.7%) cases were from colon and all the cases were adenocarcinoma and rest of all (42.3%) were from rectum.33 (63.5%) cases were Grade-I, 8 (15.4%) were Grade-II, and 11 (21.2%) were Grade-III. Only 8 (15.4%) of 52 cases showed HER2 positive, 4 (50.0%) cases were from grade- Iand another 4 (50.0%) were grade- II tumours. HER2 overexpression were significantly associated with well differentiated CRC than poorly differentiated (p=0.044). Conclusion: HER2/neu protein expression was observed in colorectal cancer but HER-2/neu protein is less likely to be expressed in colon cancer cell lines among our patients. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 52-56